Effect of Different Levels of Salivary pH on the Shear Bond Strength of Two Orthodontic Adhesive Systems for Bracket Placement: An In-vitro Study - Angelita Leonarda Carpio Contreras; Abraham Meneses López; Luis Ernesto Arriola-Guillén (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this study was to compare the effect of four different salivary pH levels on the shear bond strength (SBS) of two orthodontic adhesive systems for bracket placement. Materials and Methods: This in-vitro experimental study was performed on 72 premolars extracted for orthodontic reasons. They were randomly assigned into two groups according to the adhesive system employed: Orthocem (light-cure adhesive, FGM®) or Transbond-XT (3M Unitek). Each group involved nine specimens incubated in artificial saliva at four pH levels regarding previous studies: acidic pH (4.8 and 5.8), control pH (6.8) and alkaline pH (7.8), during two months. Once removed, shear bond strength with a universal testing machine was applied. The SBS comparisons between adhesive systems was obtained using t-test and for salivary pH levels in each group one-way ANOVA and Tukey tests were used (P < 0.05). Results: Transbond-XT adhesive system showed the greater SBS, mainly in the neutral salivary pH (11.18 ± 2.82 Mpa) followed by the alkaline (10.33 ± 2.49 Mpa) (P > 0.05). Significant differences were found regarding to both acidic pH levels (pH 4.8 and 5.8) with values between 6 and 8 MPa (P < 0.05). Moreover, Orthocem adhesive system had lower SBS values, with greater value in the neutral salivary pH (6.24 Mpa), don't achieved significant differences with the other pH levels; 4.74 Mpa for pH 4.8 and 5.05 Mpa for pH 5.8. Conclusion: Transbond XT orthodontic adhesive system showed only greater values of SBS only for the control and alkaline pH levels; for acidic pH levels there was no difference between the two systems. This situation must be taken into account by clinicians.